The role of preschoolers’ home literacy environment and emergent literacy skills on later reading and writing skills in primary school: A mediational model - Bigozzi, Lucia; Vettori, Giulia; Incognito, Oriana (Frontiers in Psychology, 2023)
The importance of the quality of home literacy environment and practices (HLE&P) in the earliest years on children’s reading and writing development is recognized in the literature. However, whether and to what extent this relationship between preschoolers’ HLE&P on their later reading and writing skills in primary school is mediated by emergent literacy competence remains to be clarified. It may be that preschool constitutes a significant opportunity for children to develop notational awareness and phonological awareness which are emergent literacy skills that are fundamental for later reading and writing skills. Children who experience literacy-poor HLE&P with fewer opportunities to practice more complex language skills and diverse vocabulary might develop adequate reading and writing skills when their emergent literacy skills in preschool are high (notational and phonological awareness). This longitudinal study aimed to investigate the mediational role of preschoolers’ emergent literacy skills in preschool (notational and phonological awareness) in the relationship between HLE&P and reading and writing skills shown by the same children in primary school using a large-scale dataset. A total of 115 children (mean-age at last year of preschool = 4.88±.36) took part in the research. In preschool, children performed emergent literacy tasks and their parents completed a home literacy questionnaire. Later, in primary school, children completed standardized assessments of spelling (orthographic accuracy and fluency in a dictation task) and reading decoding (accuracy and speed in a text reading task) skills. The results of mediational analyses showed that notational awareness totally mediates the relationship between HLE&P and reading speed (𝛽=-.17, p<.05) and writing accuracy (𝛽=.10, p<.05), but not for reading accuracy in primary school. The mediational model with phonological awareness as mediator was not significant. The results are discussed in the light of the effect of preschool in contributing to filling children’s home literacy gaps and disadvantages. In preschool, emergent literacy programs are essential to counterbalance the needs of preschoolers to develop adequate reading and writing skills when the family cannot provide enriched HLE&P from the early years of life.